Implementasi Fatwa DSN-MUI No 108/DSN-MUI/X/2016 Pada Usaha Kolam Renang Muslimah ACM - Bahri, Saiful; Khadafi, Muammar (Journal of Fiqh in Contemporary Financial Transactions, 2024)
This research aims to analyze the implementation of DSN-MUI fatwa No.108/DSN-MUI/X/2016 concerning Guidelines for Organizing Tourism Based on Sharia at ACM Muslimah swimming pools. The research uses a qualitative and normative.The research results show that the swimming pool has partially implemented sharia principles, but there are still aspects that need improvement. The facilities for places of worship are small and need to be enlarged, while some areas around the pool are still not clean. Transactions and agreements in tourism activities need to pay more attention to sharia principles. Improvements to facilities in places of worship and increased cleanliness around pools are recommended to ensure compliance with the DSN-MUI fatwa. By making these improvements, the swimming pool can provide a better experience to visitors and be more consistent with the applied sharia principles.